Criteria-based audit on management of eclampsia patients at a tertiary hospital in Dar es Salaam, Tanzania - Lindmark Gunilla; Massawe Siriel N; Mogren Ingrid; Kidanto Hussein; Nystrom Lennarth (BMC, 2009)
Abstract Background Criteria-based audits have been used to improve clinical management in developed countries, but have only recently been introduced in the developing world. This study discusses the introduction of a criteria-based audit in a tertiary hospital in an African setting, assesses the quality of care among eclampsia patients and discusses possible interventions in order to improve the quality of care. Methods We conducted a criteria based audit of 389 eclampsia patients admitted to Muhimbili National Hospital (MNH), Dar es Salaam Tanzania between April 14, 2006 and December 31, 2006. Cases were assessed using evidence-based criteria for appropriate care. Results Antepartum, intrapartum and postpartum eclampsia constituted 47%, 41% and 12% of the eclampsia cases respectively. Antepartum eclampsia was mostly (73%) preterm whereas the majority (71%) of postpartum eclampsia cases ware at term. The case fatality rate for eclampsia was 7.7%. Medical histories were incomplete, the majority (75%) of management plans were not reviewed by specialists in obstetrics, specialist doctors live far from the hospital and do not spend nights in hospital even when they are on duty, monitoring of patients on magnesium sulphate was inadequate, and important biochemical tests were not routinely done. Two thirds of the patient scheduled for caesarean section did not undergo surgery within agreed time. Conclusion Potential areas for further improvement in quality of emergency care for eclampsia relate to standardizing management guidelines, greater involvement of specialists in the management of eclampsia and continued medical education on current management of eclampsia for junior staff.